2015
DOI: 10.5604/12321966.1185763
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal microbiological quality of air in veterinary practices in Poland

Abstract: Numerous studies focused on the bioaerosols in the areas of industry, agriculture and animal husbandry, concerning both residential and public buildings, have been conducted continuously for many years. The aim of the present work was to determine the concentration and composition of mesophilic bacterial flora in the air of selected medical and veterinary clinics located in the cities and in the countryside. Air sampling was carried out in 2011-2013 in 44 veterinary practices in autumn-winter and spring-summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
2
7
0
8
Order By: Relevance
“…A similar seasonal pattern in microbial counts was also reported by Premila in residential dwellings in India [48], by Caballero et al in Mexico [49], Huang et al in Taiwan [50] and Awadh et al in Egypt [51]. In contrast to seasonal patterns observed in the present study, a study by Leppanen et al [52] in Finland, Haas et al [53] in Austria and Sitkowska et al [54] in Poland observed a rising count of microbes in the air from winter to spring and summer. The differences between observed patterns may be due to different geographic locations and climatic variability.…”
Section: Seasonal Variation In Indoor Bioaerosol Countssupporting
confidence: 91%
“…A similar seasonal pattern in microbial counts was also reported by Premila in residential dwellings in India [48], by Caballero et al in Mexico [49], Huang et al in Taiwan [50] and Awadh et al in Egypt [51]. In contrast to seasonal patterns observed in the present study, a study by Leppanen et al [52] in Finland, Haas et al [53] in Austria and Sitkowska et al [54] in Poland observed a rising count of microbes in the air from winter to spring and summer. The differences between observed patterns may be due to different geographic locations and climatic variability.…”
Section: Seasonal Variation In Indoor Bioaerosol Countssupporting
confidence: 91%
“…animal excreta and body fluids). Occupational exposure to zoonotic diseases is a risk in veterinary medicine (Weese et al 2002, Sitkowska et al 2015. In these studies an assessment of the mycological quality of air in animal veterinary practice was made.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, direct contact between veterinarians and diagnosed animals is associated with the risk of biological contamination. In veterinary practice, not only animals are sources of microorganism contamination, but also people or the components of the indoor environment (Sitkowska et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Для передачі інфекції потрібні три елементи: джерело патогенів, сприйнятливий організм та шлях передачі (Kukhtyn et al, 2017;Kozlovska et al, 2017;. Часто такі умови створюються у закритих приміщеннях, а особливо у ветеринарних клініках, оскільки забруднювачами повітря є біоаерозолі (Steneroden et al, 2010;Sitkowska et al, 2015). Біоаерозоль -це сукупність мертвих та живих патогенних і непатогенних мікроорганізмів, клітин епітелію, шерсть, волосся, частинки рослинного походження тощо, які завислі в повітрі (Harper et al, 2013;Feßler et al, 2018).…”
Section: вступunclassified